In Vitro Screening For Phytochemical And Antimicrobial Activity Of Poisonous Plant Ficus Tseila Roxb - RAMESH K. SATDIVE; RAGHURAM CHIMATA; AJAY NAMDEO; DEVANAND P. FULZELE (International Journal of Pharma and Bio Sciences, 2012)
Leaves of Ficus tsiela were extracted with different solvents and evaluated the phytochemical analysis and antimicrobial activity. The presence of biological constituents namely terpenoids, tannins, steroids, anthraquinones, flavonoids, saponins, cardiac glycosides and phlobatannin were confirmed through preliminary phytochemical analysis. Alkaloid was absent in all the extracts treated with different solvents investigated. The presence of these bioactive constituents was associated with the antimicrobial activity of the plants. Agar well diffusion method revealed all the solvent extracts exhibited antimicrobial activity. Similarly, no antimicrobial activity was observed with the aqueous extracts, although high activity was exhibited with the ethanol, moderate activity with methanol and mild activity with chloroform extracts. The Gram-negative bacteria appeared to be more susceptible to the antimicrobial effect of the extracts than the Gram-positive organisms. The results confirmed that F. tsiela could be used as source of drugs to fight infections caused by susceptible bacteria. To the best of our knowledge, this may be the first report on antimicrobial activity that has not been previously reported and phytochemical screening is also observed for the first time from the extracts of F. tsiela.